MODEL KOMUNIKASI INTERAKSIONAL ANAK AUTIS DI SEKOLAH DASAR NEGERI INKLUSI - EKA SAFITRI, YUFITA (Jurnal Pendidikan Khusus, 2017)
ABSTRACT: In this descriptive study, looking at the implementation of interactional communication model by autistic children in inclusive schools shows the difference of autistic children ability in communicating both in conveying messages and receiving messages. On the other hand requires teachers of both classroom teachers and special escort teachers to help improve the communication of children with autism in inclusive schools. The purpose of this study is to describe the implementation of interactional communication model of autistic children with regular children, classroom teachers, and GPK in SDN inclusion Tlogopatut 1 Gresik, describe the obstacles experienced by children with autism when communicating with regular children, classroom teachers and GPK in SDN inclusion Tlogopatut 1 Gresik, and describes solutions that have been given by class teachers and special escort teachers in developing the communication of autistic children in SDN Tlogopatut 1 Gresik inclusion. This research uses descriptive method with qualitative approach. Based on data analysis, it is found that the implementation of interactional model of interactional communication in inclusion schools has been done well. In sending messages and receiving messages autistic children can quite do it. In the implementation of interactional communication model three children with autism have been able to do both in the regular class and the source class. While the five students have not been able to do well. The obstacles experienced in the implementation of interactional communication model of autistic children with classroom teachers, friends, and GPK is the language factor. Most classroom teachers in inclusive schools still can not understand what the autistic child says. Because not all children with autism can speak with verbal words or use expressive language. In overcoming these obstacles the teacher provides several solutions to improve the communication of children with autism in SDN Tlogopatut 1 Gresik inclusion is by providing individualized learning programs tailored to the ability of the child, often - often invite communication children with autism so they are accustomed to communicate with others, and provide The addition of new vocabulary for autistic children to communicate by saying the word or in sentence form well. Keywords: interactional communication,  school inclusion